Table of Content - - (Journal of Risk and Crisis Management, 2025)
:Table of Content • The Role of Strategic Management in Dealing with Risks Facing Companies: An Analytical Study in the Kingdom of Saudi Arabia – 2025 Dr. Hanan Abdullah Natheer • The Role of Financial Risk Management in Promoting Sustainable Development: An applied study on Saudi sports clubs 2025 Co-Prof. Noureldaim Eltayeb Yousif Elhag • An Intelligent Model for Predicting and Preventing Overcrowding Incidents in Holy Sites Using Artificial Intelligence Technologies Mr. Abdulrahman Abdulmatlob Alsulami